Companion Skills for Local Food Tourism Village Facilitators to Improve the Family Economy of Ngemplak Dusun, Sumber Suko Village, Wagir District, Malang - Purwito, Lasi; Zulkarnain, Zulkarnain; Miroso Raharjo, Kukuh; Avrilianda, Decky (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Ngemplak Hamlet is one of the hamlets in Sumbersuko village in Wagir District, especially located on the slopes of Mount Kawi. Wagir District is located between the slopes of Mount Kawi. This hamlet is one of the hamlets in Sumbersuko village that has physical potential in terms of abundant natural resources, especially in the food sector. The people of Ngemplak Hamlet are able to make various food preparations that come from local food ingredients. Nowadays, tourists are starting to like tourist attractions that not only provide natural beauty but also community interaction. The local food village tourism facilitator has the role of providing information to tourists about the local culinary specialties that exist and the typical dishes of the people in Sumbersuko Village that are served to tourists. The concept of local food tourism villages will indirectly require the community, especially village youth, to act as facilitators of local food. However, the lack of information regarding the potential of villages in Ngemplak hamlet by the community, especially teenagers, especially regarding local food, is one of the obstacles when tourists come to their area. There is a need for assistance to prepare teenagers in Ngemplak Hamlet to be trained to increase their knowledge and skills as local food facilitators, which can be an added value for visiting tourists. The objectives of community service are as follows: (1) Empowering teenagers as facilitators of local food tourism villages in increasing their knowledge and skills in processing local food in Ngempalk Village Hamlet; (2) Provide assistance to the management and members of the local food tourism village in Ngemplak Hamlet, Sumbersuko Village in introducing the tourism village through social media; (3) Provide assistance to local food education tourism village administrators in managing the tourism village so that it can run and survive as one of the tourist village destinations in Malang Regency.